Entering the spotlight: hepatitis B surface antigen–specific B cells - Neumann-Haefelin, Christoph (J Clin Invest, 2018)
Hepatitis B virus–specific (HBV-specific) T cells have been identified as main effector cells in HBV clearance. In contrast, B cells producing neutralizing antibodies against the HBV surface antigen (HBsAg) have been studied in little detail, mainly due to methodical limitations. In this issue of the JCI, two reports use a new technique to specifically detect and characterize HBsAg-specific B cells ex vivo. Indeed, these cells are present, but show phenotypic alterations and impaired function during acute and chronic HBV infection. Thus, HBsAg-specific B cells are a novel attractive target for antiviral strategies toward functional cure of chronic HBV infection.